2016
DOI: 10.1038/nature17939
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson-associated risk variant in distal enhancer of α-synuclein modulates target gene expression

Abstract: Genome-wide association studies (GWAS) have identified numerous genetic variants associated with complex diseases but mechanistic insights are impeded by the lack of understanding of how specific risk variants functionally contribute to the underlying pathogenesis1. It has been proposed that cis-acting effects of non-coding risk variants on gene expression are a major factor for phenotypic variation of complex traits and disease susceptibility. Recent genome-scale chromatin mapping studies have highlighted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
431
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 472 publications
(451 citation statements)
references
References 58 publications
15
431
3
2
Order By: Relevance
“…As a proof of principle, we describe below how we recently applied the aboveelucidated approach to sporadic Parkinson's disease as a prototypical complex disorder, to identify common risk variants in non-coding distal enhancer elements that functionally modulate the risk to develop the disease (Soldner et al 2016). Parkinson's disease is the second most common chronic progressive neurodegenerative disease, with a prevalence of more than 1% in the population over the age of 60.…”
Section: Functional Analysis Of Parkinson's Disease-associated Risk Vmentioning
confidence: 99%
See 3 more Smart Citations
“…As a proof of principle, we describe below how we recently applied the aboveelucidated approach to sporadic Parkinson's disease as a prototypical complex disorder, to identify common risk variants in non-coding distal enhancer elements that functionally modulate the risk to develop the disease (Soldner et al 2016). Parkinson's disease is the second most common chronic progressive neurodegenerative disease, with a prevalence of more than 1% in the population over the age of 60.…”
Section: Functional Analysis Of Parkinson's Disease-associated Risk Vmentioning
confidence: 99%
“…As for SNCA, a gene known to be variable between neuronal cell types such as astrocytes, oligodendrocytes and neurons and to be regulated during development and terminal differentiation, cellular heterogeneity and incomplete maturation significantly interfere with the detection of subtle differences in gene expression between distinct risk-genotypes or patient compared to control cells, respectively. Indeed, individual in vitro differentiation experiments from genetically identical sub-clones resulted in up to fourfold differences in SNCA expression (Soldner et al 2016). To address this problem, we recently described an experimental approach that is based on determining the effect of individual regulatory elements on the transcription of the cis-regulated gene by analyzing allele-specific gene expression (Soldner et al 2016).…”
Section: Allele-specific Gene Expression As a Robust Read-out To Analmentioning
confidence: 99%
See 2 more Smart Citations
“…Soldner et al [4] used clustered regularly-interspaced short palindromic repeats (CRISPR)/Cas9 (CRISPR-associated protein 9), a powerful gene-editing technique, to analyze variants in the SNCA gene which encodes a-synuclein. They found that a common variant in a non-coding distal enhancer element increases the expression of SNCA by affecting the sequence-dependent binding of transcription factors (TFs).…”
mentioning
confidence: 99%